Influence of urban form on the performance of road pavement solar collector system: symmetrical and asymmetrical heights - Nasir, Diana S.N.M.; Hughes, Ben Richard; Calautit, John Kaiser (Elsevier, 2017)
Recent works have highlighted the importance of mitigating the urban heat island effect using innovative technologies. Several studies have emphasised the capabilities of the road pavement solar collector system to dissipate high temperature from the pavement/road surfaces not only to expand its lifecycle but also to reduce the Urban Heat Island effect. This study builds on previous research combining an urban configuration and a road pavement solar collector system in Computational Fluid Dynamics in order to understand the complicated connection of the urban environment and the road pavement. This study investigates the impact of the urban form on the performance of the road pavement solar collector focusing on comparing symmetrical and asymmetrical height of the urban street canyon. A tridimensional de-coupled simulation approach was used to simulate a macro domain (urban environment) and micro domain, which consists of road pavement solar collector pipes. ANSYS Fluent 15.0 was employed with the solar load model, Discrete Ordinate radiation model and Reynold Averaged Navier Stokes with standard k-epsilon equation. The simulation was carried out based on the summer month of June in Milan urban centre, Italy. Results showed a significant variation in the temperature results of road surface in comparing the three configurations. It was also found that there was a significant reduction in the road pavement solar collector system performance when taller building row was behind the first approaching building row. The method presented in this research could be useful for studying the system integration in various urban forms.